Neuroprotection, HMGR inhibition, vitamin E quantification and antimicrobial properties of palm puree / Nordalilah Rosni - Rosni, Nordalilah (2015)
Palm Puree (PP) is a value-added product prepared from squeezed fruitlets of oil palm fresh fruit bunches. Fiber was incorporated at different percentages for samples T24 and PT99 at 2% and 5% fiber incorporated for each sample, respectively. The study was carried out to determine the potential nutritional benefits of PP such as neuroprotection, 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGR) inhibition and antimicrobial properties. Neuroprotection properties were observed in infant brain cancer; human neuroblastoma cell line SH-SY5Y differentiated by treatment of retinoic acid and induced with H2O2. The samples gave negative neurotoxicity results and promising neuroprotective effects on 80% confluent SHSY5Y cell line in 96 well plates at a dose dependent manner. PT99 displayed most protection against H2 0 2 -induced cell lines and followed by T24 at 100 (ig/mL (p<0.05). The HMGR inhibition assay aims to find the cholesterol lowering ability of PP using pravastatin, a known HMGR inhibitor as control. T24/5 gave a considerably better oxidation of NADPH at 0.159 Units/mgP, followed by PT99/5 (0.009 Units/mgP) as compared to pravastatin. Antimicrobial testing against selected pathogenic bacteria and fungi infecting human were performed using well diffusion method at concentrations of 200 (ig/ml, 300 (ig/ml, 500 (xg/ml, 800 fig/ml and 1 mg/ml. The test showed negative results as no inhibitory activities were observed. The HPLC analysis showed that the four vitamin E derivatives identified in all PP samples were a-T3, y-T3, 8-T3 and a-TP. T24 exhibited significantly (p<0.05) higher total amount of vitamin E as compared to PT99. In conclusion, PP can be used as a healthy value-added product for human consumption.